Bioactive interpenetrating polymer network hydrogels that support corneal epithelial wound healing - Myung, David (2009)
We describe the development and characterization of collagen-coupled poly(ethylene glycol)/poly(acrylic acid) (PEG/PAA) interpenetrating polymer network hydrogels. Quantitative amino acid analysis and FITC-labeling of collagen were used to determine the amount and distribution of collagen on the surface of the hydrogels. The bioactivity of the coupled collagen was detected by a conformation-specific antibody and was found to vary with the concentration of collagen reacted to the photochemically functionalized hydrogel surfaces. A wound healing assay based on an organ culture model demonstrated that this bioactive surface supports epithelial wound closure over the hydrogel but at a decreased rate relative to sham wounds. Implantation of the hydrogel into the corneas of live rabbits demonstrated that epithelial cell migration is supported by the material, although the rate of migration and morphology of the epithelium were not normal. The results from the study will be used as a guide toward the optimization of bioactive hydrogels with promise in corneal implant applications such as a corneal onlay and an artificial cornea.